Study guide, International economics - Raymond, Arthur (Upper Saddle River, N.J. : Prentice Hall, 1998)
This book is about: International trade theory; International trade policy; balance of payments and exchange rates; ...
Keywords: Economics; International trade; International trade -- Problems, exercises, etc; International finance -- Problems, exercises, etc; International economic relations -- Problems, exercises, etc